Key determinants of students’ mobile phone choice - Michael Dzigbordi Dzandu; Henry Boateng; Cynthia Esinu Dzandu (Management Science Letters)
As there is still only limited research on students brand choice of mobile phones, the focus of this study was to ascertain drivers of tertiary students’ mobile phone brand choice in Ghana. Using a structured questionnaire, data was collected from a random sample of 840 students from three tertiary institutions in Ghana. The study revealed that the most significant determinant of the students brand choice of mobile phones was perceived quality (p<0.05). Although price, prestige, and promotion also influenced their choice of mobile phone these were not significant at the 0.05 level. The study further revealed that availability and mobile phones as gift items also influenced the brand of phone used by the students (p>0.05). The study concludes that in spite of their economic handicaps, students brand choice was driven most by perceived quality and not price. Recommendations on how information technology manufacturers’ particularly mobile phone companies and marketers can exploit these drivers to sustain and improve their brand equity among students have been made.